2017
DOI: 10.1101/240770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scalable volumetric imaging for ultrahigh-speed brain mapping at synaptic resolution

Abstract: 2We describe a new light-sheet microscopy method for fast, large-scale and imaging methods were developed to overcome this problem [9][10][11][12][13][14][15] . Recent 50 advances along this line was able to push the imaging speed to ~3 days per 51 . CC-BY-NC-ND 4.0 International license not peer-reviewed) is the author/funder. It is made available under aThe copyright holder for this preprint (which was . http://dx.doi.org/10.1101/240770 doi: bioRxiv preprint first posted online Dec. 29, 2017; 3 mouse bra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…It can image a whole mouse brain at a voxel size of 0.75 × 0.75 × 2.5 μm within 14 hours. Bi et al recently reported a technique called VISoR [21]. In this technique, the mouse brain is first sectioned into 300 μm thick slices.…”
Section: Introductionmentioning
confidence: 99%
“…It can image a whole mouse brain at a voxel size of 0.75 × 0.75 × 2.5 μm within 14 hours. Bi et al recently reported a technique called VISoR [21]. In this technique, the mouse brain is first sectioned into 300 μm thick slices.…”
Section: Introductionmentioning
confidence: 99%